2013
DOI: 10.1002/mrm.24740
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution mouse kidney perfusion imaging by pseudo‐continuous arterial spin labeling at 11.75T

Abstract: pCASL was successfully applied at very high field for mouse renal blood flow measurements, demonstrating high sensitivity, flexibility and multislice imaging capability. pCASL may be considered as a method of choice for mouse kidney perfusion studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
3
19
1
Order By: Relevance
“…In addition, the perfusion in the renal cortex was visibly increased relative to that in the renal medulla, as expected. Importantly, mouse kidney perfusion was approximately twice that of brain perfusion, consistent with previous reports . The mean perfusion value in the paraspinal muscles was 81 mL/min/100 g, which was significantly lower than that of the kidneys, as expected .…”
Section: Resultssupporting
confidence: 91%
“…In addition, the perfusion in the renal cortex was visibly increased relative to that in the renal medulla, as expected. Importantly, mouse kidney perfusion was approximately twice that of brain perfusion, consistent with previous reports . The mean perfusion value in the paraspinal muscles was 81 mL/min/100 g, which was significantly lower than that of the kidneys, as expected .…”
Section: Resultssupporting
confidence: 91%
“…Hence, for multislice 2D imaging, pCASL sSE EPI should be preferred. 9 Though, one should note that this technique provided the largest group standard deviations, which potentially indicated larger error measurements and lower robustness. However, signs of better individual accuracy toward high blood flow values, only detectable with short acquisition train length, should not be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…7T), thus resulting in long longitudinal relaxation time (T 1 ) and, therefore, enhanced the sensitivity of ASL techniques. Concerning the ASL scheme strategy, it has been recently demonstrated that, despite modest inversion efficiency, 9 the pCASL approach 2 provides several advantages compared with the widely used pulsed FAIR 14 technique 10,11,13 for mouse kidney perfusion measurement. For the readout strategy, several options are offered, among them EPI (echo planar imaging), RARE (rapid acquisition with relaxation enhancement), TrueFISP (true fast imaging with steady state precession), GRASE (gradient and spin echo), 15 UFLARE (ultra fast low angle rate) 16 or even spiral imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The images were reconstructed with zero-filling to a matrix of 128x96, resulting in apparent resolution of 0.14x0.14mm 2 . Perfusion imaging was acquired by pCASL [25][26] with labeling offset=12mm, labeling duration=1600ms, 10 post-labeling delays (PLDs) ranging from 0 to 400ms and SE-EPI with acquisition parameters the same as the T 1 mapping sequence except TR=4000ms and 30 measurements, i.e. 15 control and label pairs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%